Literatur Review : Pengembangan Biskuit Ubi Jalar, Sebagai Solusi KEK Pada Ibu Hamil. - Anis Ervina; Rita Nurhayati; Tita Wati (Akademi Kebidanan La Tansa Mashiro, 2021)
Chronic Energy Deficiency (CED) is a condition in which a pregnant woman suffers from a lack of food intake that lasts for a long time (chronic or chronic) which results in health problems, so that an increase in nutrient requirements during pregnancy cannot be fulfilled. Pregnant women who suffer from KEK have a risk of sudden maternal death during the perinatal period or the risk of giving birth to a baby with low birth weight (LBW). In Puskesmas Lebak Regency in 2016 to 2018 the number of CED pregnant women amounted to 4,615 people, increasing in 2017 to 4,758 people and in 2018 there were 8,659 people. The purpose of this study is to help the existing problems in the community so that every year pregnant women who lack chronic energy do not increase, making biscuits from purple sweet potatoes can be consumed by CED pregnant women and women throughout the life cycle. Along with the human need to improve nutrition, and to use local food, the community is increased to consume purple sweet potato biscuits as an additional food supplement. The ingredients for making purple sweet potato biscuits are used, namely: Purple Sweet Potato Flour, milk, flour, eggs, sugar and butter. It is recommended for pregnant women to consume purple sweet potato biscuits a maximum of 8 pieces per day to meet additional nutritional needs, to prevent stunting in newborns due to CED.